2014
DOI: 10.4102/sajcd.v61i1.62
|View full text |Cite
|
Sign up to set email alerts
|

National survey of paediatric audiological services for diagnosis and intervention in the South African private health care sector

Abstract: Diagnosis of hearing loss, hearing aid fitting and audiological intervention is delayed significantly in the South African private health care sector. Improved services should include integrated systematic hospital-based screening as part of birthing packages with diagnostic referral to specialist paediatric audiologists for accurate assessment and management of patients in a timely manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…It is widely reported that without UNHS, identification of hearing impairment may be as late as two years of age (Butler et al, 2015; Khoza-Shangase and Harbinson, 2015; Meyer et al, 2014; Storbeck and Young, 2016; Swanepoel et al, 2013), following suspicion of the hearing impairment typically after critical periods of language development milestones have passed (Joint Committee on Infant Hearing, 2007). Similarly, seven of the eight children in the current study were suspected as presenting with hearing impairment after the age of 12 months and as late as 4 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely reported that without UNHS, identification of hearing impairment may be as late as two years of age (Butler et al, 2015; Khoza-Shangase and Harbinson, 2015; Meyer et al, 2014; Storbeck and Young, 2016; Swanepoel et al, 2013), following suspicion of the hearing impairment typically after critical periods of language development milestones have passed (Joint Committee on Infant Hearing, 2007). Similarly, seven of the eight children in the current study were suspected as presenting with hearing impairment after the age of 12 months and as late as 4 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…These negative effects can be further exacerbated by the poor socio-economic conditions and burdened healthcare systems characteristic of developing contexts such as South Africa (Meyer et al, 2012). However, children with hearing impairment can develop speech and language abilities on par with peers with normal hearing, if the hearing impairment is identified early enough and intervention is initiated timeously (Meyer et al, 2014). Hence, universal newborn hearing screening (UNHS) is either recommended or already practiced and legally regulated in many developed countries (Lasisi et al, 2014; Petersen and Ramma, 2015; White et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar suboptimal provision of amplification devices in the South African context has been reported. In a national survey of paediatric audiology services conducted by Meyer et al (2014), suboptimal provision of amplification devices at ages older than 2 years was reported. These findings demonstrate poor adherence to the HPCSA (2018) guidelines for best practice, which recommend provision of amplification devices within 1 month of identification of the hearing impairment.…”
Section: Resultsmentioning
confidence: 99%
“…This finding once again highlights the need for comprehensive EHDI infrastructure. Through such EHDI programmes, children with a hearing impairment can experience the optimal benefits from the earliest possible hearing identification and intervention (Meyer et al, 2014). It is possible for children with a hearing impairment to achieve age-appropriate speech and language outcomes (Fulcher, Purcell, Baker, & Munro, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation